(untitled) (International Journal of Management and Sustainability, 2014)
The study examined the interactive relationship between job involvement, job satisfaction, organisational commitment citizenship behaviour (OCB) and organisational commitment among employees of Nigerian universities. The sample for the study consisted of two hundred and ten academic members of staff (210) from five (5) Federal Government owned universities in the Niger Delta Region of Nigeria. The study utilized both quantitative data (questionnaire) and qualitative data (interview). The Multiple Regression Model using the Statistical Package for Social Sciences (SPSS) version 18 were utilized for the analysis of data. The findings revealed that job involvement had a strong positive and significant relationship with organisational commitment and OCB. Although the relationship between job involvement and employees job satisfaction was also positive, it was however weak. Similarly, job satisfaction was revealed to have a positive and significant relationship with organisational commitment and OCB. Finally, organisational commitment was revealed to have a positive and significant relationship with OCB. Based on the findings above, it was concluded that as an employee develops a favourable attitude toward one aspect of the job based on unique experiences (e.g job involvement), such an employee is also likely to react favourably to other related aspects of the job (e.g job satisfaction, organisational commitment, OCB and organisational commitment). Thus, employees who are involved in their job, for example, are likely to be satisfied with the job, become committed to their organization and by extension exhibit OCBs. Similarly, employees who are dissatisfied with their job may become less involved in the work, less committed to their employer and organisation and lack OCBs. Other managerial implications of these findings were also discussed.